Pengaruh Penerapan Remedial terhadap Hasil Belajar Siswa Kelas XI pada Mata Pelajaran Kimia - Ramadani Hsb, Putri Rizkika; Nugraha, Asep Wahyu (ARKA INSTITUTE, 2022)
A research has been conducted to analyze the effect of remedial application on the learning outcomes of high school class XI students on Hydrocarbon material with the aim of knowing: (1) learning outcomes of students who do not apply remedial, (2) learning outcomes of students after remedial treatment, (3) the effect of remedial application on learning outcomes, and (4) students' perceptions of hydrocarbon learning. The results showed that: (1) the average value of the pretest was 62.22. (2) After remedial treatment for 4 times (5 times posttest) the results were obtained: posttest 1 with an average of 75.28, posttest 2 with an average of 72.22, posttest 3 with an average value of 78.18, posttest 4 with an average of 90, and posttest 5 with a value of 70. (3) the effect of remedial on student learning outcomes can be seen from the decrease in students who take remedial classes and also the average value that increases gradually for each remedial class conducted. (4) Based on the results of the questionnaire given, it can be concluded that students in both experimental classes like learning chemistry. This shows that students' motivation towards learning chemistry is quite good.